Hasil Tanaman Bawang Merah Varietas Lokananta di Tanah Ultisol Bangka dengan Pemberian Jenis Pupuk Kandang - Jaya, Indra; Mustikarini, Eries Dyah; Lestari, Tri (Journal Galung Tropika, 2025)
The production of shallot varieties is influenced by the adequacy of nutrients and soil conditions. Soil that has low nutrient content requires high nutrient input. Ultisol soil is one of the marginal soils, this soil requires additional nutrients from the right type of manure to increase crop yields. The study aims to determine the type of manure that can increase the yield of Lokananta shallots on ultisol soil. The research location is in Pangkalpinang City, Bangka Belitung Islands Province. The research period is from October 2024 to April 2025. The eksperiment used a Randomized Block Design, consisting of 4 groups based on the size of the bulbs used as seeds. The treatments were 5 types of manure (chicken, cow, goat, swallow, and bat) and control (without additional fertilizer). The parameters observed were plant height, number of leaves, number of shoots, stem diameter, bulb diameter, wet weight of bulbs, dry weight of bulbs, and yield per plot. The harvested bulbs were analyzed for water content, reducing sugar, and essential oils (VOC). The results of the study showed that the best type of manure is that derived from chicken manure. Chicken manure has been proven to be able to increase the number of leaves, number of shoots, and number of plant bulbs, tends to be higher in yield of bulbs per plant. Red onion bulbs have the highest reducing sugar content in the chicken manure treatment, while the lowest water content is found in bat manure.